Symbolic Clothing in Schools: What Should Be Worn and Why - Vucaj, Indrit (Journal of Interdisciplinary Studies in Education, 2019)
Aiming to criticize sorts of sometimes covert and oftentimes overt differences among Canada, France, the U.K. and the U.S., Symbolic Clothing in Schools is unequivocally the voice of social justice when it comes to symbolic clothing in schools. A strong advocate of symbolic clothing in schools, the author attempts to equate clothing to one’s identity in ways that promote one’s personal and cultural identity. This book is more than an extraordinary work of clothing symbolism. It is an unapologetic call for any community to accept clothing a symbol of one’s identity. Moreover, it embraces a perspective that goes beyond religion, and it encompasses various political and social dimensions.